2020
DOI: 10.1111/jvh.13362
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics in patients with SARS‐CoV‐2/HBV co‐infection

Abstract: , coronavirus pneumonia caused by SARS-CoV-2 infection has become prevalent globally 1. So far, there have been almost 2 million patients infected by SARS-CoV-2 2 , becoming a huge threat to global health. In addition to fever, dry cough, weakness and breathing difficulty, abnormal liver function may occur in considerable proportion of SARS-CoV-2infected patients (14.8%-76.3%) 3-7. Although the exact mechanism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 11 publications
3
63
2
3
Order By: Relevance
“…Therefore, only patients with SARS-CoV-2 and chronic HBV coinfection were enrolled. Although we did not compare coronavirus disease 2019 (COVID-19) patients with HBV coinfection and patients with SARS-CoV-2 infection alone in our study, Chen et al 1 found no significant differences in liver function parameters, discharge rate, length of stay, severity, and mortality between COVID-19 patients with and without HBV infection. We fully agree with the comment by Lv et al that “the clinical stage of included patients cannot be determined”.…”
contrasting
confidence: 56%
“…Therefore, only patients with SARS-CoV-2 and chronic HBV coinfection were enrolled. Although we did not compare coronavirus disease 2019 (COVID-19) patients with HBV coinfection and patients with SARS-CoV-2 infection alone in our study, Chen et al 1 found no significant differences in liver function parameters, discharge rate, length of stay, severity, and mortality between COVID-19 patients with and without HBV infection. We fully agree with the comment by Lv et al that “the clinical stage of included patients cannot be determined”.…”
contrasting
confidence: 56%
“…However, this appears to be rare occurrence with only a single case report of a patient with possible HBV reactivation (50). The limited evidence suggests that chronic HBV infection is not associated with worse outcomes compared to those without HBV infection (51,52).…”
Section: Hepatitis Bmentioning
confidence: 98%
“…Liver injury was observed in a small proportion of patients (14, 13.33%), which is within the range of incidence in patients with COVID-19 alone, and four (28.57%) patients with liver dysfunction progressed to acute-on-chronic liver failure. Moreover, other retrospective studies have shown that liver injury in COVID-19 patients with HBV coinfection also presents with varying degrees of elevated transaminases (such as ALT, AST, γ-glutamyl transferase, and total bilirubin), but most studies have found no significant difference in the degree of liver damage compared to that in patients with COVID-19 alone[ 22 - 26 ]. The characteristics of liver injury in patients with SARS-CoV-2 and HBV coinfection are listed in Table 1 .…”
Section: Impact Of Hbv On Covid-19mentioning
confidence: 99%